Formulation and hardness evaluation of tablets containing Citrus limon and Hylocereus polyrhizus powder using D-Optimal mixture design - Ezzah Abd Manan,; Siti Salwa Abd Gani,; Uswatun Hasanah Zaidan,; Mohd Izuan Effendi Halmi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The powder of mixed fruits that are Lemon (Citrus limon) and Red Pitaya (Hylocereus polyrhizus) was used as a nutritional supplement in tablet form for nutraceutical application. D-optimal mixture experimental design (D-Optimal MED) was employed to investigate the influence of different components on the response hardness of the tablet. For tablet formulation, magnesium stearate, A (0.2-1.0% w/w), menthol, B (0.2-1.0% w/w), lemon powder, C (1.0-10.0 w/w), maltodextrin, D (5.0 -10.0) and glucose, E (37.5-53.1%) are the variables while red pitaya powder and preservative are fixed components. The experimental data were used to analyze analysis of variance (ANOVA) and to develop a polynomial regression model for tablet hardness in terms of the five design factors considered in this study. D-Optimal MED predicted the hardness of the tablet at 8.5 kg/cm2 . The results showed that the best mixture was the formulation that included 0.66% A, 0.74% B, 6.15% C, 7.61% D and 44.34% E, with the actual hardness of the optimized tablet recorded at 8.581 kg/cm2 (R2 = 0.9925). The study demonstrated the potentiality of mixed fruit tablets as a nutritional supplement with therapeutic properties for general consumers well-being.